Adaptive Algorithm of Sensor Polling for Device Used for the Dam Condition's Diagnostics - Savrasov, F.V.; Shamin, A.A.; Meyta, R.V.; Pershin, E.A. (Key Engineering Materials, 2016)
This paper describes the purpose of device for collection and transmission of data to diagnose the condition of the dam, the structure of the application software and the features of the system. This paper also describes an adaptive algorithm of sensor polling designed for operation on dams. Advantages and disadvantages of this algorithm are presented.